Verbal ability from adolescence to early adulthood: A longitudinal twin study - Bratko, Denis (Array, 2004)
This paper presents the results of the longitudinal twin study of verbal ability. The aim was to explore the stability and change of word fluency and vocabulary from adolescence to early adulthood. The sample consisted of 125 same sex twin pairs (55 identical and 70 fraternal twin pairs ; 71 male and 54 female twin pairs). The samplewas recruited through the population registry, and it was representative for the city of Zagreb, Croatia. The mean age of twins at the first measurement point was 17 years, and the test-retest interval was exactly 4 years. The two factors of verbal abilities were measured: word fluency and vocabulary. The data were analyzed in order to assess phenotypic stability and change, heritability, and genetic and environmental contribution to the contiunity and change of verbal ability from adolescence to early adulthood. The results indicate a change of the mean levels, and a substantial stability of individual differences. As expected, mean scores in the second measurement point increased. The four-year phenotypic test-retest correlations were .71 and .74 for word fluency and vocabulary, respectively. Heritability of the measures of word fluency and vocabulary were very high, both for the first and second measurement points. Longitudinal analysis indicates that phenotypic stability of individual differences from adolescence to early adulthood is genetically mediated.